Variables influencing the elementary education IDEB in public municipal networks of São Paulo in 2017 (Educação e Pesquisa, 2021)
Considering the continuous need to improve the condition of Brazilian education and the moment of renewal of the main Law on financing education in municipalities in 2020, this article aims to identify the variables of the context of elementary education networks in São Paulo municipalities, which have a significant correlation with the IDEB, in 2017. Among those indicated in the literature, 33 variables are used, which have data available on official government websites, and analyzed using the Ordinary Least Squares (OLS) method and the stepwise procedure. The regression equation obtained in the study shows that the average expenditure per student on staff of the municipal networks, teaching effort, school dropout, as well as the development index of the income dimension explain, with a statistical significance of 5%, more than 66% of IDEB of municipal networks in the state of São Paulo in 2017. The results corroborate the national and international literature regarding the figure of the teacher, his remuneration, and the management of the school process as the key elements for the development of education. The moment calls for a posture of better investments, with coherent planning and execution in the social and economic context, specific to the development of educational activity, with attention to school spaces, financial resources and the professionals who work there.